Tenure Trials in Postsecondary Dance: Making Your Case. Issue 2 (3rd April 2019) - Risner, Doug; Barr, Sherrie
ABSTRACT: This professional development article focuses on the promotion and tenure dossier and the ways in which candidates can make their own best case. The authors look closely at three primary documents the candidate not only prepares but also possesses considerable control over in content, tone, and message. The Teaching Portfolio provides a forum for illustrating highly effective teaching and the candidate's pedagogical values and commitments. The annotated Professional Record (or Institutional CV) documents the candidate's achievements in scholarship, creative activity, service, honors and awards, and teaching record. The Personal Statement (or Research Statement) affords the candidate an opportunity to translate achievements into narrative form—illuminating the candidate's expertise and academic journey while highlighting research, creative activity, and teaching accomplishments as appropriate. Recently tenured faculty and senior faculty mentors provide important insights and recommendations, while the authors offer tips and practical tasks for preparing tenure and promotion materials.